Methods in Cancer Stem Cell Biology - Afify, Said M.; Seno, Masaharu (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book describes the use of stem cells and cancer stem cell generation in the inflammatory microenvironment (cancer-inducing niche) using induced pluripotent stem cells. It provides step-by-step techniques and manuals for studying stem cell and cancer stem cell generation with different applications in cancer research. The development of induced pluripotent stem cells has provided a new approach to studying cancer initiation by producing cancer stem cells without introducing mutations or foreign genes. The book features the research of the authors' group, which was the first to generate cancer stem cells from stem cells in the presence of inflammatory conditions. The 20 chapters if this book cover topics such as generating pluripotent stem cells, converting normal stem cells to cancer stem cells, enriching, isolating and evaluating cancer stem cells. Methods for evaluating the characteristics of cancer stem cells and possible therapies against them are also discussed. The book provides easy-to-follow protocols that help researchers in the study of cancer stem cells. Illustrations help readers understand how the method of cancer stem cell generation can be applied as an essential method for assessing the carcinogenic potential of various non-mutagenic compounds. It will be a useful resource for graduate students, researchers, technicians, and physicians working in academic, hospital, and pharmaceutical settings. .
1. On the origin of cancer -- 2. Culture of Cells: Basic Principles -- 3. Stem cell culture from embryos -- 4. Reprogramming of normal cells -- 5. Maintenance of human Pluripotent Stem Cells -- 6. Identification of cancer stem cells by different molecular markers -- 7. Enrichment of Cancer Stem Cell from malignant tumor -- 8. Isolation of single clonal cell from primary cultured cells and establishment of a cancer stem cell line -- 9. Artificial Generation of Cancer Stem Cells from Normal Stem Cells -- 10. Quick method to assess non-mutagenic carcinogens with iPS cells -- 11. Self-renewal potential of caner stem cells -- 12. Differentiation potential of cancer stem cells in vitro -- 13. Tumor Angiogenesis by cancer stem cells in vivo -- 14. Invasion and Metastatic potential of cancer stem cells in vitro -- 15. Metastatic potential of cancer stem cells In Vivo- 16. Anchorage-independent cell growth assay for Cancer Stem Cells: Tumorigenic assay in vitro -- 17. Tumorigenic potential of cancer stem cells in vivo -- 18. Development of immunoliposomes using monoclonal antibodies targeting cancer stem cells -- 19. In-vitro evaluation of anti-cancer stem cell drugs -- 20. In vitro Tumoroid Model Using Cancer Stem Cells.
Keywords: Cancer; Biology -- Technique; Stem cells; Cancer Biology; Biological Techniques; Cancer Stem Cells; Stem Cell Biology